Plants Seem Prima Facie Indian but Alien In Origin : A Nomenclatural Chaos - Patil, D A; Khairnar, S B (Plantae Scientia, 2021)
The alien species, as the native ones, are assigned two names. These are based on choice of nomenclaturist. The nominclaturists are preforce been forced to adapt the scientific names in accordance with the rules and principles of ICN (International Code of Nomenclature) for uniformity and convenience internationally. The present authors could notice some plant taxa which by their names and on etymological analysis, prima facie, appear to be Indian species. The fact is, however, contrary. When select 26 such species were studied critically for their nativity consulting relevant literature, they turned out to be aliens. Maximum alien species belong to various parts of American continent, while other regions or countries are represented by a few or a single species each. The taxa which appear to be Indian but basically they are aliens, a new term ‘pseudo-native’ for them is proposed. The authors also pointed out necessity to have evaluation regarding exotic status of species of flora of a region for better management of plant-wealth in future.